The Effect Of Social Media Use, Entrepreneurial Knowledge, And Self-Efficacy On Students' Interest In Entrepreneurship In The City Of Bengkulu - Danofi, Alwin; Susanti, Neri; Yustanti, Nirta Vera (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The purpose of this study is to examine whether there is an influence of social media use, entrepreneurial knowledge and self-efficacy on entrepreneurial interest in students in Bengkulu City. The method used in this study is a quantitative method where data is obtained through distributing questionnaires to respondents. This study focuses on management students of class 22 of the Faculty of Economics and Business, Dehasen University, Bengkulu. Based on the characteristics of the study, a sample of 61 people was obtained. The results of this study show the results of multiple regression Y = 3.863 + 0.417 X1 + 0.341 X2 + 0.243 X3, the results of the t-test X1 0.001, X2 0.005 and X3 0.032 the results of the three variables are below 0.05, the results of the F test 0.000 <0.05 the results state that the variables of social media use, entrepreneurial knowledge and self-efficacy have a positive and significant effect on entrepreneurial interest in students in Bengkulu City. And the results of the determination coefficient test in this study were 0.527, which means that the independent variable had an influence of 52.7% on the Y variable.